The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1001/archneur.65.4.540
|View full text |Cite
|
Sign up to set email alerts
|

Carbon 11–Labeled Pittsburgh Compound B Positron Emission Tomographic Amyloid Imaging in Patients With APP Locus Duplication

Abstract: To investigate amyloid accumulation by carbon 11-labeled Pittsburgh Compound B (11 C-PiB) in hereditary cerebral amyloid angiopathy and APP locus duplication. Design, Setting, and Patients: Positron emission tomography with 11 C-PiB and magnetic resonance imaging were performed for 2 patients, 49-year-old and 60-yearold siblings with APP locus duplication, with hereditary Alzheimer disease and cerebral amyloid angiopathy. Main Outcome Measure: Change in 11 C-PiB uptake. Results: Uptake of 11 C-PiB was increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 14 publications
7
31
1
1
Order By: Relevance
“…1 One way to investigate the pathologic changes present in the earliest phase of AD is to study familial AD mutation carriers. Recently, 11 C-PIB PET studies have been performed in such patients and interestingly point mutations 30 and deletions 31 in both symptomatic and asymptomatic carriers of the presenilin-1 gene and duplication of the amyloid precursor protein locus 32 have all been shown to lead to increases in 11 C-PIB uptake, which are predominantly striatal-a pattern distinct from that seen in sporadic AD. Follow-up studies will reveal how the pattern of 11 C-PIB uptake will evolve with the development and progression of clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…1 One way to investigate the pathologic changes present in the earliest phase of AD is to study familial AD mutation carriers. Recently, 11 C-PIB PET studies have been performed in such patients and interestingly point mutations 30 and deletions 31 in both symptomatic and asymptomatic carriers of the presenilin-1 gene and duplication of the amyloid precursor protein locus 32 have all been shown to lead to increases in 11 C-PIB uptake, which are predominantly striatal-a pattern distinct from that seen in sporadic AD. Follow-up studies will reveal how the pattern of 11 C-PIB uptake will evolve with the development and progression of clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…PiB-PET studies showed that Aβ load was highest in the striatum of presymptomatic individuals carrying autosomal dominant mutations in the presenilin 1 and amyloid precursor protein genes (20,21). The present study shows that Aβ deposition is more prominent in the cortical than in the subcortical regions in NL FH+ individuals at risk for LOAD.…”
Section: Discussionmentioning
confidence: 99%
“…An early high PIB retention in the striatum was reported in presymptomatic carriers of presenilin-1 mutation (132). Similarly, an increased PIB uptake also in the striatum and posterior cingulate was observed in patients with amyloid precursor protein locus duplication and cerebral amyloid angiopathy (133). Compared with a sporadic-AD patient, a familial-AD patient who carried His163Tyr mutation in the presenilin-1 gene showed high PIB retention in the striatum but also in the posterior cingulate cortex and the thalamus (39).…”
Section: Amyloid Imagingmentioning
confidence: 77%